Desain Pop Up Book Sebagai Media Pembelajaran Pada Materi Tata Surya di SMP/MTs - Harahap, Nirwana; Afrida, Juniar; Aida, Nur (Desultanah: Journal Education and Social Science, 2023)
Abstract This study aims to design pop up book learning media on solar system material to determine the feasibility of pop up book learning media on solar system material. This research uses the type of research and development (R &; D) 4D model developed by Thiagarajan which has several stages consisting of the defining stage (define), design (design), development (develop) and testing stage (disseminate). The instrument used in this study is an expert validation sheet consisting of two experts, namely media experts and learning material experts. (1) pop up book learning media design is equipped with materials, mini games, LKPD, UNBK competency tests, moving images when opened and illustrations that attract the attention of students. (2) The design of this pop up book is made attractive and the results of media expert validation get with a feasibility percentage of 87.7% in the very feasible category while the results of material expert validation get a feasibility percentage of 94, 9% in the very feasible category. then pop-up book media is categorized as very suitable for use in Solar System material. Abstrak Penelitian ini bertujuan untuk mendesain media pembelajaran pop up book pada materi tata surya untuk mengetahui kelayakan media pembelajaran pop up book pada materi tata surya. Penelitian ini menggunakan jenis penelitian research and development (R & D) model 4D yang dikembangkan oleh Thiagarajan yang memiliki beberapa tahapan terdiri dari tahap pendefinisian (define), perancangan (design) pengembangan (develop) dan tahap menguji coba (disseminate). Instrumen yang di gunakan dalam penelitian ini merupakan lembar validasi ahli yang terdiri dari dua ahli yaitu ahli media dan ahli materi pembelajaran. (1) desain media pembelajaran pop up book dilengkapi dengan materi, mini game, LKPD, uji kompetensi UNBK, gambar yang bergerak jika dibuka dan ilustrasi yang menarik perhatian peserta didik. (2) Desain pop up book ini dibuat menarik dan hasil validasi ahli media mendapatkan dengan persetase kelayakan 87,7% berkategori sangat layak sedangkan hasil validasi ahli materi mendapatkan persentase kelayakan 94, 9% berkategori sangat layak. maka media pop-up book dikategorikan sangat layak digunakan pada materi Tata Surya.